2012
DOI: 10.1161/circoutcomes.112.965632
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence, Practice Guidelines, and β-Blocker Utilization Before Major Noncardiac Surgery

Abstract: Background-Largely on the basis of 2 randomized trials published in the 1990s, β-blockers were initially promoted as an evidence-based intervention for preventing cardiac complications of noncardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…2,6 Similar findings have been recently reported by Canadian investigators during this timeframe. 5 We were unable to demonstrate significant differences between our post hoc definitions of long-term use or acute institution of ␤-blockade. Limited evidence suggests that long-term use of ␤-blockade is associated with lower rates of adverse outcome than institution within 1 week of or immediately after surgery.…”
Section: Discussionmentioning
confidence: 65%
“…2,6 Similar findings have been recently reported by Canadian investigators during this timeframe. 5 We were unable to demonstrate significant differences between our post hoc definitions of long-term use or acute institution of ␤-blockade. Limited evidence suggests that long-term use of ␤-blockade is associated with lower rates of adverse outcome than institution within 1 week of or immediately after surgery.…”
Section: Discussionmentioning
confidence: 65%
“…A recent AHA systematic review [23] supporting the updated recommendations on perioperative beta blockade identified 17 studies, all but two initiated a beta blocker 1 day or less before surgery. The pooled data of studies starting beta blockers 1 day or less before surgery showed a reduction in nonfatal myocardial infarction, but increased rates of stroke, death, hypotension, and bradycardia.…”
Section: Beta Blockersmentioning
confidence: 99%
“…Hospitals and clinical departments undertook strategies to promote local adherence to β-blocker guidelines 38 39. In clinical practice, use of preoperative β-blockade increased rapidly between 1999 and 2005,40 reflecting one observer's sentiment that ‘the paradigm is shifting from predicting which patient is at high risk…to minimizing the likelihood of such an event with specific perioperative pharmacologic therapy’ 41…”
Section: Construction Of An Evidence-based Practice: the Emergence Ofmentioning
confidence: 99%